Plasticity of recurrent inhibition in the Drosophila antennal lobe - RAMASWAMI, MANI (My University, 2012)
Recurrent inhibition, wherein excitatory principal neurons stimulate inhibitory interneurons that feedback on the same principal cells, occurs ubiquitously in the brain. However, the regulation and function of recurrent inhibition are poorly understood in terms of the contributing interneuron subtypes as well as their effect on neural and cognitive outputs. In the Drosophila olfactory system, odorants activate olfactory sensory neurons (OSNs), which stimulate projection neurons (PNs) in the antennal lobe. Both OSNs and PNs activate localinhibitoryneurons(LNs)thatprovideeitherfeedforwardorrecurrent/feedbackinhibitioninthelobe.Duringolfactoryhabituation, prior exposure to an odorant selectively decreases the animal’s subsequent response to the odorant. We show here that habituation occursinresponsetofeedbackfromPNs.OutputfromPNsisnecessaryforolfactoryhabituationand,intheabsenceofodorant,directPN activation is sufficient to induce the odorant-selective behavioral attenuation characteristic of olfactory habituation. PN-induced habit- uation occludes further odor-induced habituation and similarly requires GABA A Rs and NMDARs in PNs, as well as VGLUT and cAMP signaling in the multiglomerular inhibitory local interneurons (LN1) type of LN. Thus, PN output is monitored by an LN subtype whose resultant plasticity underlies behavioral habituation. We propose that recurrent inhibitory motifs common in neural circuits may similarly underlie habituation to other complex stimuli
PUBLISHED
Keywords: Genetics